2006
DOI: 10.1021/jp063003s
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies on the Low-Lying Electronic States of the HSO Neutral Radical and Its Cation

Abstract: Using the complete active space self-consistent field (CASSCF) method with large atomic natural orbital (ANO-L) basis set, four electronic states of the HSO neutral radical are optimized. The vertical transitions of the HSO neutral radical are investigated by using the same method under the basis set of ANO-L functions augmented with a series of adapted 1s1p1d Rydberg functions, through which eight valence states and eight Rydberg states are probed. Ionic states of the HSO neutral radical are extensively studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…They found that CH 3 SO has a strong excitation at 260 nm (4.77 eV) and a weak excitation at 530 nm (2.34 eV), which correspond to the (p, p*) excitation and the (n, p*) excitation respectively. The (n, p*) excitation is assigned to the D 1 state through calculations, which is consistent with previous calculations on HSO 23,24 and PhSO . 22 Some studies have been also carried out on the isomerization product R-OS .…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…They found that CH 3 SO has a strong excitation at 260 nm (4.77 eV) and a weak excitation at 530 nm (2.34 eV), which correspond to the (p, p*) excitation and the (n, p*) excitation respectively. The (n, p*) excitation is assigned to the D 1 state through calculations, which is consistent with previous calculations on HSO 23,24 and PhSO . 22 Some studies have been also carried out on the isomerization product R-OS .…”
Section: Introductionsupporting
confidence: 90%
“…21,22 There are certain studies on both the ground state and excited state. Early calculations showed that the D 1 states of HSO 23,24 and PhSO 22,25 are both (n, p*) states, at which an electron transfers from the n O orbital to the p* orbital of the S-O group, leaving the unpaired electron at the n O orbital. In 2013, Schreiner et al 26 recorded the IR and UV-vis spectra of CH 3 SO together with theoretical calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Protonated SO (HSO + ) is an especially attractive candidate for detection: it is predicted to have a closed-shell 1 A electronic ground state (Li et al 2006); the dipole moment is high (equilibrium values calculated at the CCSD(T)/cc-pwCVQZ level of theory are μ a = 2.9 D and μ b = 1.1 D; this work); and it has a rich spectrum in the millimeter and THz bands. With only two heavy atoms the lowest rotational transition of HSO + lies outside the range of our FTM spectrometer, but the same experimental techniques used here for cis-HOSO + can be applied to the laboratory search for this ion in the millimeter-band.…”
Section: Many Rotational Transitions Of Hosomentioning
confidence: 94%
“…Similar results have been presented by Wang and Howard, 24 Wilson and Dunning, 28 and Wang and Wilson 29 together with predicted vibrational wavenumbers for HSO and HOS. Li et al 30 have predicted the vertical and adiabatic ionization energies associated with four electronic states of the HSO radical. An observation of the HSO A ̃2A′−X ̃2A″ band system by chemiluminescence spectroscopy has been reported by Schurath et al; 31 these authors could assign vibronic bands with prominent ν 3 progressions of HSO for the A ̃state up to v 3 ′ = 7.…”
Section: ■ Introductionmentioning
confidence: 99%